Strategije za podnaslovno prevajanje profanosti v slovenščino - Trupej, Janko (Slavistična revija, 2015)
Based on the analysis of twenty films, the article addresses strategies for translating profanities into Slovenian in subtitling. All examples of profanity in each film were examined. It was determined to what extent profanity was preserved in the subtitles and how often it had no equivalent. A glossary of all profane translations was made for the former category, while the latter examples were categorized according to the strategy for avoiding profanity that was used: deletion, modulation of register, substitution with a pronoun, radical change of meaning. Furthermore, it was determined how often profanity was not preserved for objective reasons and how often censorship occurred. Some main characteristics of Slovenian strategies for subtitling profane language are also illustrated with the help of examples.
Keywords: angleščina; censorship; cenzura; English; English language; film; podnaslavljanje; prevajalske strategije; prevajanje; profanity; profanost; Slovene; Slovenian language; slovenščina; subtitling; translating; translating strategies; translation